Green Brands: A Strategy for Sustainable Success in Modern Markets - Hamza, Mohamed Mostafa; Kasem, Osama Hamed; Gharbiya, Ahmed Zarea (Journal of Global Economy, Business and Finance, 2025)
In today's rapidly evolving business landscape, sustainability has emerged as a defining factor in brand success. With consumers increasingly prioritizing environmental consciousness, Businesses must adapt their branding strategies to align with these values, or they risk falling behind. This paper explores the intricate intersection of branding and sustainability, offering insights into how companies can navigate this complex terrain to achieve both profitability and positive environmental impact. It investigates the evolving expectations of environmentally conscious consumers and the transformative power of sustainable branding on consumer perceptions and purchasing behaviour. One of the key challenges facing brands today is the need to authentically integrate sustainability into their identity and operations. This paper explores strategies for achieving such authenticity, emphasizing the importance of transparency, accountability, and genuine commitment to environmental stewardship. By showcasing best practices and real-world examples, this research provides actionable insights for brands seeking to forge a meaningful connection with sustainability-minded consumers. Furthermore, this paper delves into the strategic implications of sustainable branding for businesses operating in diverse sectors and markets. It examines the potential risks and rewards of embracing sustainability, from market differentiation and brand loyalty to regulatory compliance and supply chain resilience. Through a comprehensive analysis of industry trends and competitive dynamics, this study equips brands with the knowledge and tools needed to navigate the complexities of sustainable success. By embracing sustainability as a core value proposition, brands can not only enhance their competitive advantage but also contribute to the collective effort towards a more environmentally sustainable future. In summary, this paper serves as a comprehensive guide for brands seeking to navigate the challenges and opportunities of sustainability in the modern marketplace, offering practical strategies and insights to drive sustainable success.